2004
DOI: 10.1007/s00296-003-0329-9
|View full text |Cite
|
Sign up to set email alerts
|

Familial Mediterranean fever and glomerulonephritis and review of the literature

Abstract: Familial Mediterranean fever (FMF) is an autosomal recessive disease characterized by recurrent and self-limited attacks of fever usually accompanied by polyserositis. Amyloidosis is its most common renal complication. A number of reports have shown vasculitic diseases such as polyarteritis nodosa and Henoch-Schönlein purpura affecting the kidney in FMF. Here we present a patient with FMF and membranoproliferative glomerulonephritis and analyze the data published on these two entities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 14 publications
2
28
1
Order By: Relevance
“…Four patients using regular colchicine, two were found to have MsPGN and two were found to have MGN. These findings are inconsistent with other publications that suggest a protective role of regular colchicine for GN [25] . Homozygosity for the M694V mutation is a major risk factor for renal amyloidosis in FMF patients [14] .…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Four patients using regular colchicine, two were found to have MsPGN and two were found to have MGN. These findings are inconsistent with other publications that suggest a protective role of regular colchicine for GN [25] . Homozygosity for the M694V mutation is a major risk factor for renal amyloidosis in FMF patients [14] .…”
Section: Discussioncontrasting
confidence: 57%
“…With colchicine and angiotensin converting enzyme inhibitors, a marked improvement was seen in patients with amyloidosis, but no improvement was seen in patients with FSGS [24] . Akpolat T et al have suggested that colchicine prevents glomerular disease, and that the irregular use of this drug triggers GN attacks [25] . In our study, four of nine patients were diagnosed as FMF and were receiving regular colchicine before biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…9 Akpolat et al described a 25-year-old patient, whose proteinuria remitted partially with prednisolone and azathioprine, who had membranoproliferative glomerulonephritis with FMF. 12 Immune complexes are exhibited in 50% of FMF patients. 6 IgM, IgA, and C3 deposits found in the mesangium in previously reported cases 3,6,11 are supportive of immunologic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Prednisolone, cyclophosphamide, and azathioprine have been rarely used in cases with FMF-related glomerulonephritis, 3,12 but colchicine is the most common drug used to treat FMF-associated glomerulonephritis. 12 Said et al documented important improvement in three patients with IgM nephropathy and FMF who took regular treatment with colchicine.…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports showed that FMF patients with non-amyloid renal involvement -including IgG and IgM mesangial proliferative glomerulonephritis and IgA nephropathy -also responded to colchicine therapy alone 13,14 . This observation suggests that colchicine may suppress the inflammatory process affecting the kidneys.…”
Section: Rheumatologymentioning
confidence: 99%